Penerapan Metode Pembelajaran Reward And Punishment dalam Keterampilan Berbicara Bahasa Jerman - karmilawati, karmilawati; Azizah, Laelah; Saleh, Nurming (Universitas Negeri Makassar, 2021)
This research is a classroom action research which consists of two cycles, each cycle consisting of the planning stage, the implementation stage, the observation and reflection stages. The purpose of this study was to determine the German speaking skills of class XII IIS 2 SMA Negeri 11 Makassar through the reward and punishment learning method. The subjects of this study were 34 students of class XII IIS 2. The research data consists of two types, namely quantitative and qualitative data. Qualitative data were obtained through observation sheets and quantitative data were obtained through speaking skills tests in cycles I and II. Data were analyzed using percentage techniques. The results of this study indicate that speaking skills with the percentage of scores obtained by students in the first cycle reached 65.970% and 77.352% in the second cycle increased (12%). This shows that the application of the Reward and Punishment learning method improves the speaking skills of class XII IIS 2 SMA Negeri 11 Makassar.